Redeeming Relationship, Relationships that Redeem Free Sociability and the Completion of Humanity in the Thought of Friedrich Schleiermacher - Robinson, Matthew Ryan (Mohr Siebeck, 2018)
Beziehungen, die erlöst werden und erlösen. Freie Geselligkeit und die Vollendung der Menschheit im Denken Friedrich Schleiermachers.
PublicationDate: 20180911
Keywords: Theology -- Religious Studies -- Philosophy of Religion -- Jürgen Basedow -- Sociology of Religion -- interreligious dialogue -- Practical Theology -- Systematische Theologie -- Religionsphilosophie -- Praktische Theologie -- Antike Religionsgeschichte -- Array